2014
DOI: 10.1111/gcb.12648
|View full text |Cite
|
Sign up to set email alerts
|

Phenological response to climate change in China: a meta‐analysis

Abstract: The change in the phenology of plants or animals reflects the response of living systems to climate change. Numerous studies have reported a consistent earlier spring phenophases in many parts of middle and high latitudes reflecting increasing temperatures with the exception of China. A systematic analysis of Chinese phenological response could complement the assessment of climate change impact for the whole Northern Hemisphere. Here, we analyze 1263 phenological time series (1960-2011, with 20+ years data) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
233
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 345 publications
(267 citation statements)
references
References 30 publications
28
233
3
3
Order By: Relevance
“…Therefore, at high latitude, the contribution of stronger warming to advancing trend in spring phenophases can be partly or totally offset by the weaker temperature sensitivity there. This explains why the latitude is not an important predictor of the strength of phenological trends, as suggested by previous studies (Ge et al 2014a;Matsumoto 2010;Parmesan 2007).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, at high latitude, the contribution of stronger warming to advancing trend in spring phenophases can be partly or totally offset by the weaker temperature sensitivity there. This explains why the latitude is not an important predictor of the strength of phenological trends, as suggested by previous studies (Ge et al 2014a;Matsumoto 2010;Parmesan 2007).…”
Section: Discussionsupporting
confidence: 50%
“…For example, spring/summer phases of plants advanced by 2.5 days/decade from 1971 to 2000 in Europe (Menzel et al 2006). Similarly, in China, obvious advancing trend of 2.75 days/decade f or spring/summer phenophases over the past 50 years was found (Ge et al 2014a). Spring phenology in the continental United States (except the southeastern part) became 4-8 days earlier after 1984 compared to proceeding decades (Schwartz et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cong et al [18] found that the vegetation green-up onset date advanced at the rate ranging from 0.4 to 1.9 days per decade (depending on the methods used) over temperate China in the period 1982-2010. In a recent meta-analysis of trends among Chinese plant phenophases, the spring phenophases of woody and herbaceous plants also advanced over the past several decades [3], suggesting that the variability of plant phenophases as seen from the ground is in accordance with the spatially integrated date of SOS observed from space.…”
Section: Discussionmentioning
confidence: 87%
“…Among various types of phenotypic plasticity (e.g., morphological, physiological, behavioral, phenological), phenology is particularly sensitive to small variations in environmental factors [2]. Recent meta-analyses showed that most time series of spring phenophases (e.g., flowering and leaf unfolding time of plants) arrived earlier in response to climate warming over the past several decades, and the magnitude of these advances are comparable across continents [3][4][5]. Regarding phenophases of plant senescence, the overall trend is towards later phenophases mainly due to the remarkable autumn warming, but the trends were less apparent and exhibited distinct regional difference [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation phenology indicates the response and adaptation of terrestrial ecosystems to climatic and environmental changes [1,2], and is critical for understanding the effects of these changes on the carbon cycle [3], water cycle [4] and energy exchange [5] of terrestrial ecosystems. In the Indian monsoon region, the growth of vegetation is mainly controlled by precipitation [6,7], which has experienced significant changes in intensity and frequency over the past half-century [8][9][10]; these changes will certainly cause shifts in vegetation phenology, such as a significant advance in the start of growing season (SOS) in northern parts (e.g., Punjab, Haryana) of India [11].…”
Section: Introductionmentioning
confidence: 99%